Risk Study of Cayenne Pepper and Tomato Farming in Suralaga District, East Lombok - Vita Diana; Halil; Pande Komang Suparyana (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2024)
West Nusa Tenggara Province is one of the central areas for developing horticultural commodities, including cayenne pepper and tomato plants. High production not balanced by market demand can cause cayenne peppers and tomatoes to be sold at lower prices. The purpose of this study was to analyze the level of risk of production, price, and income of cayenne pepper and tomato farming in Suralaga District, East Lombok Regency. This study was conducted in Suralaga District, East Lombok Regency in Kerongkong Village and Suralaga Village. Respondents in this study were cayenne pepper and tomato farmers in the Suralaga District totaling 60 respondents. Risk measurement uses the method of variance, standard deviation, and coefficient of variation. The results of the study showed. The level of risk of cayenne pepper farming is greater or riskier than tomato farming, both in terms of production risk, price risk, and income risk. In cayenne pepper farming, the production risk is KV = 0.16 / Ha is greater than the risk of tomato production of KV = 0.11 / Ha. The risk of cayenne pepper price, which is KV=0.04, is greater than the risk of tomato price, which is KV=0.01. The risk of cayenne pepper farming income, which is KV=0.18/Ha, is greater than the risk of income in tomato farming, which is KV=0.11/Ha. 1. It is expected that cayenne pepper farmers will optimize the use of inputs, especially fertilizers so that the production produced is high with good quality. Meanwhile, tomato farmers are expected to think about off-farm, namely processing agro-industry, to be able to get higher added value.